Governments that Achieve Results : Introducing Performance Mechanisms and Exploring the Trust Dimension - Felcman, Daniela (World Bank, Washington, DC, 2012)
Over the past few decades, a significant number of advanced countries and, more recently, some developing countries have moved the focus of their budget arrangements to emphasize performance. The recently published book results, performance budgeting and trust in Government follows from a conference on performance budgeting held in Mexico in June 2008 where a large range of experiences from Latin America and Organization for Economic Co-operation and Development (OECD) countries was presented. Its intention is to provide readers and governments wishing to improve elements of their performance budgeting with an understanding of the many elements involved in implementing these reforms, particularly in performance-informed budgeting (PIB), focusing on the challenges and the variety of approaches taken to meet these challenges. In many OECD and middle income countries, performance budgeting has been associated with the use of modern techniques of public management that emphasize individual and organizational responsibility and accountability for results. The books starts by providing an overview of PIB, building on two decades of experience and lesson learning, and sets out the key themes that provide the basis for discussions in the subsequent chapters. It looks at the roles of key decision-makers and institutions in creating a network of structured performance agreements4 throughout the budget cycle.